YAP and TAZ are required for the postnatal development and the maintenance of the structural integrity of the oviduct. Issue 2 (August 2020) - Godin, Philippe; Tsoi, Mayra; Paquet, Marilène; Boerboom, Derek
Abstract : The development of the Müllerian ducts into the female reproductive tract requires the coordination of multiple signaling pathways that regulate proliferation, apoptosis and differentiation. The Hippo pathway has been reported to interact with several pathways with established roles in Müllerian duct development; yet, its potential roles in reproductive tract development and function remain mostly uncharacterized. The objective of this study was therefore to characterize the roles of the Hippo transcriptional coactivators YAP and TAZ in the female reproductive tract using transgenic mouse models. This report shows that the concomitant conditional inactivation of Yap and Taz in the mouse Müllerian duct mesenchyme results in postnatal developmental defects of the oviduct. Most notably, discontinuities in the myosalpinx layer lead to the progressive formation of cystic dilations of the isthmus. These defects prevented embryo transport and subsequent implantation in older animals, causing infertility. The loss of YAP/TAZ did not appear to affect other biological processes known to be required for the maintenance of oviductal wall integrity, such as TGF-β/SMAD and Notch signaling and the biogenesis of miRNA, suggesting that the Hippo pathway acts independently of these processes to direct oviduct development. Taken together, these results suggest redundant and essential roles for YAP and TAZ in the postnatal development of the oviduct and the maintenance of its structural integrity.